Structural, electronic and optical properties of Fe(III) complex with pyridine-2,6-dicarboxylic acid: A combined experimental and theoretical study - La Porta, Felipe A. [UNESP]; Ramos, Paulize H.; Resende, Eliane C. de; Guerreiro, Mario C.; Giacoppo, Juliana O. S.; Ramalho, Teodorico C.; Sambrano, Julio R. [UNESP]; Andres, Juan; Longo, Elson [UNESP] (Elsevier B.V., 2014)
This paper describes the synthesis, as well the structural, electronic and optical properties of a novel complex of Fe(III) with pyridine-2,6-dicarboxylic acid (DPA). The complex was characterized by Fourier transform infrared (FT-IR) spectroscopy, Fourier transform Raman spectroscopy (FT-Raman), field emission scanning electron microscopy (FE-SEM), UV-Vis absorption spectroscopy and photoluminescence (PL) measurements. The chemical compositions were examined with an energy dispersive X-ray spectrometer (EDXS) analysis. First principle calculations at density functional theory (DFT) level have been carried out in order to understand the effects caused by structural distortions. The synthesized iron complex shows a molar ratio of 1:2 metal/ligand with an approximate octahedral configuration. Theoretical results derived from the analysis of molecular orbitals (MOs) and the electron density obtained from Quantum Theory of Atoms in Molecules (QTAIM) point out that the chemical bonds between oxygen and the iron atom in the Fe-DPA complex is predominantly electrostatic. In order to modeling the PL emissions, an energy profile associated to the variation of the dihedral angle (C-N-N-C) of the Fe-DPA complex, connecting the ground and excited electronic states, allows us to find a relationship between structural order-disorder effects with PL emissions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Pyridine-2,6-dicarboxylic acid; Coordination compound; Iron complex; Optical properties; DFT